2014
DOI: 10.1155/2014/701316
|View full text |Cite
|
Sign up to set email alerts
|

Sanitary Conditions of Food Vending Sites and Food Handling Practices of Street Food Vendors in Benin City, Nigeria: Implication for Food Hygiene and Safety

Abstract: Objective. To determine the sanitary conditions of vending sites as well as food handling practices of street food vendors in Benin City, Nigeria. Methodology. A descriptive cross-sectional study was done using an observational checklist and researcher-administered questionnaire. 286 randomly selected vending units were surveyed, and their operators interviewed on their food handling practices. Results. A higher proportion, 259 (90.5%), of the observed vending sites appeared clean. The following sanitary facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
92
8
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(117 citation statements)
references
References 11 publications
14
92
8
3
Order By: Relevance
“…e greater proportion of females who were street food vendors in this study reflects the sociocultural role of women in food preparation and serving in Ghana. Similar findings have been reported in Benin City, Nigeria [20], Ethiopia [21], and Uganda [6]. In countries such as Haiti [22] and Kenya [23], it was reported that street food vendors were predominantly males.…”
Section: Discussionsupporting
confidence: 84%
“…e greater proportion of females who were street food vendors in this study reflects the sociocultural role of women in food preparation and serving in Ghana. Similar findings have been reported in Benin City, Nigeria [20], Ethiopia [21], and Uganda [6]. In countries such as Haiti [22] and Kenya [23], it was reported that street food vendors were predominantly males.…”
Section: Discussionsupporting
confidence: 84%
“…17 Studies like Bamidele et al, Rahman et al and Cuprasittrut et al had shown poor hygiene practice among food handlers, whereas a contrasting result is seen in some studies where more than half of the respondents were having good practice. 14,[18][19][20][21][22] Significant association (p<0.05) between practice and socio demographic characteristics like education, marital status and type of food vendor was found, suggesting practice is not only dependent on knowledge and attitude but is also influenced by several other socio demographic factors.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a need to generate food and personal hygiene, and to ensure an effective system of regular hygienic-sanitary examinations with vendors and regular sample collections of the foodstuffs sold to customers [37]. Food vendors are recommended to maintain standard environmental and personal hygiene while preparing, packaging or serving food products to consumers [38]. Proietti et al [39] proposed specific points of attention for street food preparation and sales based on related hazard-tailored actions.…”
Section: Resultsmentioning
confidence: 99%